EVALUASI KEPUASAN PEMBELAJARAN DARING SELAMA MASA PANDEMI PADA MAHASISWA KEPERAWATAN UDAYANA - Saputra, Dimas Aji; Rahajeng, Indah Mei; Yanti, Ni Putu Emy Darma; Damayanti, Putu Ayu Asri (Coping: Community of Publishing in Nursing; Vol 11 No 2 (2023): April 2023DO - 10.24843/coping.2023.v11.i02.p14, 2023)
The COVID-19 pandemic has affected human life including education. The learning process in schools and universities shifted into online methods to prevent the spread of COVID-19. The purpose of this study was to evaluate the satisfaction level for online learning process during the pandemic among nursing students. This research was a descriptive study, the survey conducted on 170 nursing students of Udayana University in June 2022 selected by the stratified random sampling method. The results showed that respondents were aged 18-22 years old, dominantly female which were 149 students (87,6%), and respondents were majority at the second year with 49 people (28,8%). The results showed that majority students were satisfied, the evaluation of online learning in this study indicated that the level of satisfaction for online learning were on the high level, with total of 109 students (63,8%) respond. There were 89 female students (52,4%) and 40 second-year students (23,5%) responded their evaluation for online learning in the high level of satisfaction. This study concluded the respondents were dominated with female students, in their second year, aged 18-22 years old; the majority of students were satisfied for online learning at Udayana University.